2022
DOI: 10.2147/jmdh.s389932
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Multidisciplinary Extracurricular Event Using Kolb’s Experiential Learning Theory: A Qualitative Study

Abstract: Background and Purpose Although health science programs run parallel to each other and comprise of shared core subjects between the different disciplines, students of the different disciplines rarely mix or interact with each other during their undergraduate studies. Extracurricular activities are a big part of university students’ life, through which students have an opportunity to express themselves and enhance their soft skills in a safe and relaxed environment. Recently, King Saud University (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…To produce enabling beliefs and consequences, encouraging proper understanding of interdisciplinary settings and the various disciplines involved in health care can further support students' engagement in their learning. These findings align with previous research where students were reported to enjoy working collaboratively as it helps with understanding, problem-solving, and providing better patient care (5,18). If students can optimize their contributions, patient care can be positively influenced and allow for a holistic approach (19).…”
Section: Enablerssupporting
confidence: 90%
“…To produce enabling beliefs and consequences, encouraging proper understanding of interdisciplinary settings and the various disciplines involved in health care can further support students' engagement in their learning. These findings align with previous research where students were reported to enjoy working collaboratively as it helps with understanding, problem-solving, and providing better patient care (5,18). If students can optimize their contributions, patient care can be positively influenced and allow for a holistic approach (19).…”
Section: Enablerssupporting
confidence: 90%
“…For instance, Fewster-Thuente and Batteson describe all modes of KELT in the design and evaluation of a simulated IPE activity using a case study to explore attitudes and behaviours of interdisciplinary groups of pre-licensure students in healthcare programs [ 39 ]. Two other examples in the literature more fully explicate application and evaluation of KELT for students in other interprofessional healthcare contexts included settings specific to older adults in long term care and raising the public’s awareness of rights and responsibility in the healthcare system [ 31 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as mentioned in the introduction of Almalag et al paper, the acquisition of IP competencies during the multidisciplinary event in the study was a parallel observation noted by the authors during the event. 7 It was thought that the best way of exploring these observations would be through focus group discussions which allow participants to express their perceptions, feelings, and views freely in response to general questions that contain no reference to IPEC competencies which avoids guiding students’ answers or introducing bias, Almalag et al supplementary table. 7 As such, any themes that emerge during these discussions are representative of the students’ experience during the event.…”
Section: Dear Editormentioning
confidence: 99%
“… 7 It was thought that the best way of exploring these observations would be through focus group discussions which allow participants to express their perceptions, feelings, and views freely in response to general questions that contain no reference to IPEC competencies which avoids guiding students’ answers or introducing bias, Almalag et al supplementary table. 7 As such, any themes that emerge during these discussions are representative of the students’ experience during the event. We thus elected to use the focus group approach.…”
Section: Dear Editormentioning
confidence: 99%